Ciri-ciri jawatankuasa audit dan tahap kepatuhan laporan kewangan koperasi di Kelantan - Yusri Huzaimi, Mat Jusoh (2016)
The rate of non-compliance to financial reporting timeliness and accounting standards among the cooperatives in Kelantan is considered high comparatively. As a result, there are some cooperatives which are unable to conduct their annual general meetings (AGM) due to the failure to provide the financial reports on time. In some cases, there are several cooperatives which manage to pay dividends, yet the process exceeds the stipulated time. Thus, this study is carried out to investigate the criteria of effective and efficient audit committee in fostering compliance towards financial reporting standards. The criteria of audit committee have been taken from the best practices prescribed by the Malaysian Code on Corporate Governance, 2012 to the audit committee in public listed companies. Those characteristics include competency, independence, diligence and composition. Competency is measured by expertise and experience; independence is based on the duration of appointment and diligence by frequency of meetings. As for the composition, it is based on the size of audit committee. This study aims to help the cooperatives in Kelantan to identify the effective and efficient criteria of audit committee. The data for this study was obtained from questionnaires for audit committee characteristics and secondary data for compliance levels. A total of 177 audit committee members completed the questionnaires and the data on compliance levels were obtained from 59 cooperatives. The result of the analysis reveals that experience, duration of appointment and the size of audit committee are the significant atributes which affect the compliance with timelineness and accounting standards. Among the limitations of this study are; it was carried out in Kelantan and the data of the compliance was collected for one year only.